2017
DOI: 10.3349/ymj.2017.58.3.619
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Associations betweenCHGBGenetic Variants and Schizophrenia in a Korean Population

Abstract: PurposeSchizophrenia is a devastating mental disorder and is known to be affected by genetic factors. The chromogranin B (CHGB), a member of the chromogranin gene family, has been proposed as a candidate gene associated with the risk of schizophrenia. The secretory pathway for peptide hormones and neuropeptides in the brain is regulated by chromogranin proteins. The aim of this study was to investigate the potential associations between genetic variants of CHGB and schizophrenia susceptibility.Materials and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…Weiss’s group [17] indicated that several variants of SHANK3 had associations with SCZ. Gender-specific associations between variants of CHGB and SCZ have been revealed in a Korean population by Shin et al [15]. Conversely, a case-control study indicated that there was no significant association between SNPs of FGA and SCZ [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weiss’s group [17] indicated that several variants of SHANK3 had associations with SCZ. Gender-specific associations between variants of CHGB and SCZ have been revealed in a Korean population by Shin et al [15]. Conversely, a case-control study indicated that there was no significant association between SNPs of FGA and SCZ [19].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few decades, variants in several candidate genes, including DRD2 , ZNF804A , CHGB , NRGN , SHANK3 , BACE1 , FGA , and complement 3 ( C3 ), were found to be associated with SCZ [15-20]. Particularly, the concentration of C3 in the blood of patients with SCZ has been extensively studied, and the role of complement in SCZ is beginning to be more widely explored.…”
Section: Introductionmentioning
confidence: 99%
“…All five SNPs were associated with stress that arises due to changes in blood pressure in Southern Californians, including sub-Saharan African and European ancestry groups [33]. Moreover, two SNPs (rs6085324 and rs742711) have been associated with schizophrenia in the Korean population [19] and SNP rs236152 has also been associated with schizophrenia in the Japanese population [16].…”
Section: Chgbmentioning
confidence: 99%
“…Even so, the knowledge available on the variability and expression pattern of these neuropeptide genes in different modern human populations is limited at the moment. The majority of the studies conducted on these genes [13][14][15] so far have tended to focus on one specific neuropeptide in one specific population [11,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…in adult mouse NG2 glia [169] Modulation of neuronal activity [170] Chromogranin B, Chgb Gene expr. study of freshly sorted adult human NG2 glia [125] Neurotransmission [171,172] Chromogranin C, Chgc Gene expr. study of freshly sorted adult human NG2 glia [125] Neurite outgrowth [173] and angiogenesis [174].…”
Section: Neuregulinsmentioning
confidence: 99%